Analysis energy demand and design of solar energy in UMP mosque - Mohd Faizal, Mohd Yusof (2009)
Photovoltaic system is very popular in the renewable energy system. The improvement in the technology itself is very high. The improvement in this technology is to ensure that the system may result in low cost, high performance PV cells, long life time period, and maintenance-free lifetime. Every year engineers make an improvement on the products that have been in existence for many years. The application of this system also was acknowledgement around the world nowadays and this system was applicable in many industries. The application of this system in our country also is very efficient because of our climatic condition is suitable for this system. The most popular application of this system is the application as a supply system for the building. This project is conducted to choose the type of solar module and inverter that can be implemented to UMP mosque. At the end of this project, we will know the suitable solar module and inverter that can be implemented to UMP mosque.